The Influence Of Leadership Empowerment Behavior And Knowledge Management On Lecturers Self-Efficacy In A Public University In Saudi Arabia - Mutad Lafi H, Alharbi (2019)
This study aims to investigate the interrelation of leadership empowerment behavior, knowledge management and lecturer self-efficacy in a public university in Saudi Arabia. In addition, the role of knowledge management as a mediator on the relationship between the leadership empowerment behavior with lecturer self-efficacy is also examined. The survey methods using a questionnaire was employed in collecting data in this study. A total of 354 lecturers were selected as respondents using simple random sampling to answer the research questionnaire.